E-voting as a form of e-participation - Aleksandra CZUPRYNA-NOWAK (Communications of International Proceedings, 2021)
The consequence of the pandemic outbreak in 2019 was a worldwide lockdown, which caused the rapid development of tools and remote work methods. Remote methods have also been used in areas of life where, until now, it has not been possible to apply them. Remote learning, studying, and shopping are just areas of life that have replaced the forms that humanity knew for many months. The same happened with the methods of human communication. Also, the methods of participation or voting had to take a remote form. The article presents an outline of the methods of e-participation and e-voting in Poland and in the world.
Keywords: Remote Voting; E-Participation; E-Voting; Electronic Voting.